2015
DOI: 10.1007/s12094-014-1265-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-15a down-regulation is associated with adverse prognosis in human glioma

Abstract: These findings indicated for the first time that the expression of miR-15a is significantly correlated with prognosis in glioma patients, suggesting that the miR-15a may serve as independent prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…MiRNAs can also function as tumor suppressors. For example, Xie et al demonstrated that down-regulation of miR-15a was associated with an adverse prognosis in human glioma patients [44]. Yang et al validated the role of miR-16 as a tumor suppressor in glioma and uncovered a novel mechanism of miR-16-mediated inhibition of glioma growth and invasiveness through inhibition of BCL2 and the NF-κB1/MMP-9 signaling pathway [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs can also function as tumor suppressors. For example, Xie et al demonstrated that down-regulation of miR-15a was associated with an adverse prognosis in human glioma patients [44]. Yang et al validated the role of miR-16 as a tumor suppressor in glioma and uncovered a novel mechanism of miR-16-mediated inhibition of glioma growth and invasiveness through inhibition of BCL2 and the NF-κB1/MMP-9 signaling pathway [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…To measure the expression of miRNA-15a, all of the studies used qRT-PCR. Six of 10 studies used the exact value of miRNA expression as the cut-off value, two studies used the median value [17, 20], and the remaining two studies did not provide relevant information. [21, 22] For survival assessment criteria, all incorporated literature used OS and five studies used DFS.…”
Section: Resultsmentioning
confidence: 99%
“…Downregulation of miRNA-15a has recently been reported in patients with CLL [7], non-small-cell lung cancer [10], prostate cancer [11], ovarian cancer [12], and hepatocellular carcinoma [13]. As an important member of miRNA-15/16 cluster, the influence of miRNA-15a on the prognosis of colorectal cancer [1417], osteosarcoma [18], esophageal squamous cell carcinoma [19], glioma [20], breast cancer [21], cholangiocarcinoma [22], and multiple myeloma [23] has been reported. However, the results were insignificant or opposite.…”
Section: Introductionmentioning
confidence: 99%
“…The survival of patients was usually 14 months [17]. The adverse prognosis of patients with glioma was associated with malignant biological behavior of tumor cells, including proliferation of brain tissue surrounding the invasion and chemotherapy drug resistance [18][19][20]. It was acknowledged that the excessive proliferation of tumor cells was an important factor causing recurrence of glioma after operation [21][22][23].…”
Section: Discussionmentioning
confidence: 99%